Comparison of instrumental methods of hemostasis research - K. V. Bossenko (Kazimierz Wielki University, 2017)
Urgency of the Problem. It is known that deep vein thrombosis of the lower extremities and pulmonary thromboembolism play an important role in the structure of postoperative morbidity and mortality, and these complications are characteristic of patients with different profiles. Considering the above, we consider it important to introduce into clinical practice new diagnostic methods that would be effective, reliable, and allow us to conduct research in real time. The Objective: to compare the methods for the instrumental study of blood coagulation properties and assess the capabilities of the method of low-frequency piezoelectric thromboelastography value in clinical practice. Materials and methods. Used various methods of instrumental studies of blood coagulation properties in the study of the functional state of the hemostatic system in a group of 60 healthy volunteers, as well as 74 patients with postthrombophlebitic syndrome. The ARP-01M Mednord APC indicators were correlated with data reproducible with the TEG® 5000 apparatus. To evaluate the reproducibility of the technique, a series of measurements of hemostasis parameters in healthy volunteers was performed. Conclusion. AIC ARP-01M Mednord is a compact, convenient and safe in operation coagulology analyzer that meets all the requirements of medical equipment. Due to these qualities, it can be successfully used not only in clinical laboratories, but also at the patient's bed, in the operating room, in an ambulance car.